Predicting Tourist Loyalty to a Small Emerging Destination – The Importance of Destination Image - Nghiem-Phu, Binh (UI Scholars Hub, 2021)
In the Southeast Asia region, Vietnam is a developing country and also a developing tourism destination. The number of international tourists to Vietnam has been increasing in recent years. However, the post-trip issues (e.g., not returning, bad word-of-mouth) have become the focal points of many arguments. Based on the existing literature, this study devel- oped and tested a theoretical model to predict international tourists’ loyalty to Vietnam from a combination of destination image, tourist motivation, and overall trip satisfaction. The findings revealed that destination image significantly and positively predicted tourists’ overall satisfaction with the trip and their loyalty to the country in the future. Tourist motiva- tion had some weak but significant effects on both overall trip satisfaction and destination loyalty when tested separately; however, the effect on overall trip satisfaction could not be observed when controlled by destination image. Implications were discussed for Vietnam and other small emerging destinations.